The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1073/pnas.95.18.10938
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a calcium-sensitive nonspecific cation channel by closely associated protein kinase and phosphatase activities

Abstract: Regulation of nonspecific cation channels often underlies neuronal bursting and other prolonged changes in neuronal activity. In bag cell neurons of Aplysia, it recently has been suggested that an intracellular messengerinduced increase in the activity of a nonspecific cation channel may underlie the onset of a 30-min period of spontaneous action potentials referred to as the ''afterdischarge.'' In patch clamp studies of the channel, we show that the open probability of the channel can be increased by an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 32 publications
7
48
0
Order By: Relevance
“…It was possible to identify these channels based on their conductance (25-30 pS; ϳ2 pA at Ϫ60 mV), voltage dependence of opening (an increase in P O with depolarization), and absence of voltage-dependent inactivation. In previous work, we showed that application of ATP to the cytoplasmic face of cation channel-containing patches produced an increase in channel P O (Wilson et al, 1998;Magoski et al, 2002). We found that this increase in P O was attributable to the activity of a closely associated PKC-like kinase phosphorylating the cation channel or some adjacent protein ( Fig.…”
Section: Effects Of Atp On Cation Channel Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was possible to identify these channels based on their conductance (25-30 pS; ϳ2 pA at Ϫ60 mV), voltage dependence of opening (an increase in P O with depolarization), and absence of voltage-dependent inactivation. In previous work, we showed that application of ATP to the cytoplasmic face of cation channel-containing patches produced an increase in channel P O (Wilson et al, 1998;Magoski et al, 2002). We found that this increase in P O was attributable to the activity of a closely associated PKC-like kinase phosphorylating the cation channel or some adjacent protein ( Fig.…”
Section: Effects Of Atp On Cation Channel Activitymentioning
confidence: 99%
“…Protein kinase C (PKC) is closely associated with the cation channel. This interaction persists in excised inside-out patches and serves to enhance activity through phosphorylation of the channel (Wilson et al, 1998;Magoski et al, 2002). Following the afterdischarge, the neurons enter an ϳ18 h refractory period, during which a second afterdischarge and ensuing second bout of reproductive behaviors cannot be initiated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown that application of ATP alone to the cytoplasmic side of these patches causes an increase in open probability (P O ), suggesting that a kinase might be intimately associated with the channel. PKC inhibitor peptides blocked ATP-induced increase in P O , consistent with a PKC-like kinase (Wilson et al, 1998). Magoski and Kaczmarek (2005) reported that less than one-half of the patches containing these cation channels showed an increased channel P O in the presence of ATP, whereas the rest showed no change or a decrease in P O [Magoski and Kaczmarek (2005), their The authors investigated the molecular mechanism underlying this variable response.…”
mentioning
confidence: 99%
“…This channel is regulated by a variety of kinases and phosphatases including protein kinase C (PKC). PKC is colocalized with the cation channel in excised patches and increases channel activity via phosphorylation (Wilson et al, 1998;Magoski et al, 2002). In their recent article in The Journal of Neuroscience, Magoski and Kaczmarek (2005) showed that the state of PKC-channel interaction reflects the state of the bag cell neuron: PKC is coupled to the cation channel during the afterdischarge and uncoupled during the refractory state.…”
mentioning
confidence: 99%